ANALISA PENERAPAN PENGGUNAAN ISYARAT OLAH GERAK DI ATAS KAPAL SESUAI DENGAN COLLISION REGULATIONS 1972 - Mohamad Adam Irfandi Hidayatullah Adam Irfandi (PPPM POLTEKPEL SORONG, 2022)
Abstrack MOHAMAD ADAM IRFANDI HIDAYATULLAH, 2021, Analysis of the Application of the Use of Signal movement on Ships in Accordance with Collision Regulations 1972. Supervised by Capt. Tri Mulyatno and Novrico Susanto. Signal movement if on board is very important to note. Because it is not uncommon for ship wrecks to occur, the officer of the ship mistakes the cue or reads the cue. This might also cause the ship's officers to not understand and understand the meaning of the sign on the ship itself.Because it needed the right action to prevent and overcome this. The response is in the form of training and counseling or also in the form of providing insights in order to reduce errors in reading or giving gestures on the ship. The research will be carried out by the author carried out for approximately 1 year. Furthermore, in a literature review and frame of mind, the author will explain about the definition, Collision Regulations 1972, and actions in the installation or reading of gestures that need to be done by officers. Primary data obtained from this study were sourced from interviews conducted directly. Then the secondary data obtained from books read by the author and teaching and learning activities in class related to the object of writing. While in the framework of the author's writings put forward the writing systematic used in this Applied Scientific Work. Keywords : Signal Movement, 1972 Collision Regulation.